2005
DOI: 10.1002/ca.20065
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical consideration of vascularized bone graft transfer from the medial calcaneus to the talus

Abstract: To investigate the possibility of use of the calcaneal branches of the posterior tibial artery as the pedicle for the vascularized bone graft to the talus, a detailed anatomical study was carried out on 30 fresh cadaver feet. Although there are several branches from the posterior tibial artery to the calcaneus, the largest posterior branch was defined as the main calcaneal branch. We recognized frequently a large branch nourishing the superior part of the calcaneus and named it the superior calcaneal branch. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…One disadvantage associated with the present technique is the short vascular pedicle, and a cadaveric study 24 showed that the vascularized bone graft harvested from the medial calcaneus and transplanted to the talus does not reach far enough in 10% of cases. This procedure may not be indicated for all the patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One disadvantage associated with the present technique is the short vascular pedicle, and a cadaveric study 24 showed that the vascularized bone graft harvested from the medial calcaneus and transplanted to the talus does not reach far enough in 10% of cases. This procedure may not be indicated for all the patients.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that transplanting a bone graft with the calcaneal branch of the posterior tibial artery is anatomically possible. 24 The present study clinically applied this method and reviewed the results.…”
Section: Introductionmentioning
confidence: 99%
“…It's a challenge to deal with talar fractures because of the bone's special anatomic characteristics. The talus has no muscle or tendon attachment and about 60% of the bone surface is covered with articular cartilage, which leaves a limited region for vascularization [8,9] . The outcome of talar fractures varies widely and depends on the degree of initial damage and the accuracy of fracture reduction [10] .…”
Section: Introductionmentioning
confidence: 99%